Fluoride-bridged dinuclear dysprosium complex showing single-molecule magnetic behavior: supramolecular approach to isolate magnetic molecules - Wu, Dong-Fang; Takahashi, Kiyonori; Fujibayashi, Masaru; Tsuchiya, Naoto; Cosquer, Goulven; Huang, Rui-Kang; Xue, Chen; Nishihara, Sadafumi; Nakamura, Takayoshi (RSC advances, 2022)
Using Na-encapsulated benzo[18]crown-6 (Na)(B18C6) as a counter cation, we successfully magnetically isolated a fluoride-bridging Dy dinuclear complex {[(PW 11 O 39 )Dy(H 2 O) 2 ] 2 F} (Dy 2 POM) with lacunary Keggin ligands. (Na)(B18C6) formed two types of tetramers through C-H O, π π and C-H π interactions, and each tetramer aligned in one dimension along the c -axis to form two types of channels. One channel was partially penetrated by a supramolecular cation from the ± a -axis direction, dividing the channel in the form of a "bamboo node". Dy 2 POM was spatially divided by this "bamboo node," which magnetically isolated one portion from the other. The temperature dependence of the magnetic susceptibility indicated a weak ferromagnetic interaction between the Dy ions bridged by fluoride. Dy 2 POM exhibited the magnetic relaxation characteristics of a single-molecule magnet, including the dependence of AC magnetic susceptibility on temperature and frequency. Magnetic relaxation can be described by the combination of thermally active Orbach and temperature-independent quantum tunneling processes. The application of a static magnetic field effectively suppressed the relaxation due to quantum tunneling. (Na + )(benzo[18]crown-6) forms a bamboo-like supramolecular architecture within the crystal. Dinuclear Dy complexes with polyoxometalate ligands embedded between bamboo nodes exhibited a clear single-molecule magnet (SMM) response.